Study of Financial management - Sharma, N. R. (Universal Research Reports, 2018)
The administration of monetary resources is at the heart of financial management, which is a kind of managerial activity. In the 20th century, financial management became a distinct academic discipline. Until recently, it was employed in economics. The topic's scope has changed throughout time as an educational subject. At first, financial management was mainly concerned with raising money for the company. Modern financial management, on the other hand, views the gathering of money as just one aspect of the job; it also emphasises the effective use of those assets. Financial management now examines all of a company's financial issues.